Complete plays of Bhasa : text with eenglish translation & notes - Menon, K. P. A. (New Delhi, 1996)
This book is focused on Sanskrit Literature. The works were not being read nor his plays being enacted anywhere i the country with the exception of the narrow coastal strip of Kerala but the memory remained alive and fresh in the minds of Sanskrit scholars and literature.
Keywords: Sanskrit drama-Translation into english